Impact of parental relatedness on reproductive outcomes among the Old Order Amish of Lancaster County. Issue 7 (20th April 2022) - Lynch, Megan T.; Maloney, Kristin A.; Pollin, Toni I.; Streeten, Elizabeth A.; Puffenberger, Erik G.; Strauss, Kevin A.; ,; Shuldiner, Alan R.; Mitchell, Braxton D.
Abstract: Genetically isolated populations that arise due to recent bottleneck events have reduced genetic variation reflecting the common set of founders. Increased genetic relatedness among members of isolated populations puts them at increased risk for some recessive disorders that are rare in outbred populations. To assess the burden on reproductive health, we compared frequencies of adverse reproductive outcomes between Amish couples who were both heterozygous carriers of a highly penetrant pathogenic or likely pathogenic variant and noncarrier couples from the same Amish community. In addition, we evaluated whether overall genetic relatedness of parents was associated with reproductive outcomes. Of the 1824 couples included in our study, 11.1% were at risk of producing a child with an autosomal recessive disorder. Carrier couples reported a lower number of miscarriages compared to noncarrier couples ( p  = 0.02), although the number of stillbirths ( p  = 0.3), live births ( p  = 0.9), and number of pregnancies ( p  = 0.9) did not differ significantly between groups. In contrast, higher overall relatedness between spouses was positively correlated with number of live births ( p  < 0.0001), pregnancies ( p  < 0.0001), and stillbirths ( p  = 0.03), although not with the number of miscarriages ( p  = 0.4). These results highlight a complex association between relatedness of parents and reproductive health outcomes in this community.